2015
DOI: 10.1016/j.febslet.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the transglycosylation activity of plant family GH18 chitinase by removing or introducing a tryptophan side chain

Abstract: Edited by Miguel De la RosaKeywords: Chitinase Transglycosylation Chitin oligosaccharide Tryptophan residue Crystal structure Cycas revoluta a b s t r a c t Transglycosylation (TG) activity of a family GH18 chitinase from the cycad, Cycas revoluta, (CrChiA) was modulated by removing or introducing a tryptophan side chain. The removal from subsite +3 through mutation of Trp168 to alanine suppressed TG activity, while introduction into subsite +1 through mutation of Gly77 to tryptophan (CrChiA-G77W) enhanced TG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
(73 reference statements)
0
25
0
Order By: Relevance
“…The former inactivated TG activity while the later enhanced TG activity. This study demonstrated the importance of the side chain of aromatic residues to TG activity [ 86 ]. TG was improved by altering the substrate-interaction sites involving residues in the catalytic center, catalytic cleft, and solvent exposed region of S. proteamaculans ChiD ( Sp ChiD).…”
Section: Implications Of Variations Among Chitinases For Optimizationmentioning
confidence: 91%
See 2 more Smart Citations
“…The former inactivated TG activity while the later enhanced TG activity. This study demonstrated the importance of the side chain of aromatic residues to TG activity [ 86 ]. TG was improved by altering the substrate-interaction sites involving residues in the catalytic center, catalytic cleft, and solvent exposed region of S. proteamaculans ChiD ( Sp ChiD).…”
Section: Implications Of Variations Among Chitinases For Optimizationmentioning
confidence: 91%
“…TG takes place when retaining glycosidases trigger the transfer of a glycosidic residue (instead of a nearby nucleophilic water molecule in hydrolysis) from a donor to an acceptor yielding longer chain COS with high DP ( Figure 8 C) [ 24 ]. TG occurring during hydrolysis may be undesirable because it interrupts bond cleavage efficiency and causes misevaluation of hydrolytic activity because of the production of unexpected enzymatic products [ 86 ]. Serratia proteamaculans ChiD ( Sp ChiD) was found to exhibit ‘transglyco-hydrolytic’ activity with a hyper-TG activity on DP2 to DP6 substrates, thus generating long chain COS of DP up to 13 and a hydrolytic property that breaks down DP8 and DP10 TG products to DP2 and DP4 COS respectively [ 24 ].…”
Section: Classification Based On Differences In Catalytic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…is oriented in a way that a sugar ring can be stacked at subsite +3. Such tight substrate recognition at "plus" subsites is known to be a key determinant of transglycosylation activity in other glycoside hydrolases [50]. The tight substrate recognition also indicates that binding of M3 is stabilized at subsites +1, +2, and +3.…”
Section: Crystal Structure Of Ref-manmentioning
confidence: 93%
“…The reaction mechanism of GH 18 family enzymes is a retaining mechanism (catalysis leads to the retention of the anomeric configuration), whereas GH 19 enzymes use an inverting catalytic mechanism, resulting in anomeric inversion [8]. Plant chitinases are traditionally divided into different classes, and GH family 18 members are subdivided into the classes III and V. While there are numerous reports on class III chitinases [9], only three class V chitinases have been characterized, namely NtChiV from tobacco (Nicotiana tabacum) [10][11][12][13][14], AtChiC from Arabidopsis thaliana [15,16] and CrChiA from the gymnosperm Cycas revoluta [17][18][19][20]. Crystal structures for these three enzymes have been solved recently.…”
Section: Introductionmentioning
confidence: 99%